THU0164 Polymorphism of Cytotoxic T-Lymphocyte Antigen 4 +49A/G is Associated with Refractoriness to Non-Biological Dmards in Rheumatoid Arthritis Patients. (23rd January 2014) - Guseva, I.; Demidova, N.; Soroka, N.; Panasyuk, E.; Luchikhina, E.; Fedorenko, E.; Alexandrova, E.; Novikov, A.; Trofimov, D.; Karateev, D.; Nasonov, E.
Abstract : Background: The value of genetics markers to predict non-responders to traditional DMARDs who are in need of biological therapy has not been studied so far in rheumatoid arthritis (RA). Objectives: To investigate whether the polymorphisms of immune response genes are associated with prescribing the biological treatment in RA patients (pts) refractory to the previous therapy Methods: Two groups of RA pts were included in this study (table1). The first one included 121 early RA (eRA) pts with disease duration less than 2 years, followed up for the subsequent 4 years. All pts received non-biological DMARDs (MTX up to 20-25 mg/week in combination with other DMARDs). Non-responders to this therapy (DAS28-CRP>3, 2) were treated with biologics. The second group consisted of 43 pts with active RA (moderate to severe) enrolled in the open label, phase IV trial to confirm the effectiveness and safety Tocilizumab (TCZ) through 6 infusions (8 mg/kg) [1 ]. The previous therapy with non-biologic DMARDs was not effective in these patients. Using "gene candidate" approach we selected the following gene polymorphisms (SNPs) for genotyping: PTPN22 (+1858 C/T, rs2476601), CTLA4 (+49A/G, rs231775), TNFAIP3 ( rs675520, rs6920220), IL6 (-174G/C, rs1800795), IL6R (+358A/C, rs8192284), TNFA (-308A/G, rs1800629), MCP1/ CCL2 (+2581A/G, rs1024611), IL10 (-592A/C, rs1800872, -1082 A/G, rs1800896). Results: By the end of the follow-up period, 14 out of 121 eRA pts did not respond to DMARDs and were treated with biological. CTLA-4 gene polymorphism (+49A/G) was the only predictor for the administration of biological therapy in eRA group that was confirmed by a logistic regression analysis [OR=6, 1 95% CI 1, 4-26, 2, p=0, 01]. The carriers of GG genotype received the biological therapy more often than AA/AG genotypes carriers (5/14, 28, 6% and 9/107, 8, 4% respectively). The distribution of genotypes AA, AG and GG differed statistically between eRA and TCZ groups (33, 1%, 55, 4%, 11, 6% and 37, 2%, 37, 2%, 25, 5% respectively, p=0, 04). In TCZ group the CTLA-4(+49A/G) genotypes were associated with ESR value at baseline (AA-42, 0 (21, 1), AG-59, 3 (19, 8), GG-66, 8 (21, 8), p=0, 01). Conclusions: Our data suggest than the genetic polymorphism CTLA-4+49A/G is associated with more severe rheumatoid arthritis and may predict the need for biological therapy References: Guseva I.A., Soroka N.E., Panasyuk E.Y. et al. Ann Rheum Dis 2011;70(Suppl3):465 Disclosure of Interest: None Declared